(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The present article studies a series of objects found in the Vaccaean town of Pintia: a fragmentary inscription written on the bottom of a vase from the settlement of Las Quintanas, in a Celtic dialect possibly similar to Gaulish; a small box decorated by excision and what seems to be magic pseudowriting, found in a pit at the necropolis of Las Ruedas; eleven hallmarks of lesser or greater complexity on various types of ceramic objects found in eleven graves of the same necropolis. It seemed, moreover, appropriate to actualize the commentaries accompanying the publication of other, typologically similar hallmarks.